Evaluation of the area of applied sciences (600 Dewey) of the collection of the Library "Joaquin García Monge". - Campos Cerdas, Jorge (2005)
This research aims to determine the quality, timeliness, level of user satisfaction, use and relevance of the collection area of Applied Sciences Library "Joaquín García Monge" in relation to the needs of users.Was selected as a case study collection of the area of Applied Sciences Library "Joaquín García Monge" covering environmental science, agriculture and forestry, physics and industrial chemistry, veterinary medicine, psychiatry, management, accounting, marketing, crafts and typing. Bibliographic be evaluated solely for the collection of books and bibliographic reference.